Sustainable Production of Biodiesel Using Eggshell-Derived CaO/K₂O Catalyst: Influence of Process Variables and Factorial Design Analysis - Agung Prabowo; Syarifuddin Oko; Muh Irwan; Alvyano; Gading Bagus Mahardika (Politeknik Negeri Semarang, 2026)
This study investigates the effects of CaO/K₂O catalyst mass (X₁) and reaction time (X₂) on biodiesel yield produced from waste cooking oil via transesterification. A 2² factorial design was employed to evaluate the main and interaction effects of both parameters. Analysis of variance (ANOVA) confirmed that the developed regression model was statistically significant (p = 0.0253) with a high coefficient of determination (R² = 0.9386), indicating excellent model adequacy. The reaction time (X₂) exhibited the most significant positive effect on biodiesel yield (t = 5.96), while the catalyst mass (X₁) showed a negligible influence. The interaction term (X₁X₂) presented a moderate negative effect, suggesting that excessive catalyst loading combined with longer reaction duration may slightly decrease yield due to soap formation and emulsification. The contour profiler revealed that yield increases with both factors up to an optimum point, after which further catalyst addition provides minimal improvement. The optimum conditions were achieved at a catalyst mass of 4.5 g and a reaction time of 4.5 h, resulting in a biodiesel yield of 70.3%. These findings confirm that reaction time is the dominant factor affecting transesterification efficiency, and that CaO/K₂O derived from waste eggshells serves as an effective and sustainable heterogeneous catalyst.